Mexico and the Spanish Civil War : political repercussions for the Republican cause - Ojeda Revah, Mario (Sussex studies in Spanish history., 2015)
"Based on first-hand diplomatic, political and journalistic sources, most unpublished, Mexico and the Spanish Civil War investigates the backing of the Second Republic by Mexico during the Spanish Civil War. Significant military, material and financial aid was given by the government of Lázaro Cárdenas (1934-1940) to the Republic, which involved not only direct sales of arms, but also smuggling operations covertly undertaken by Mexican diplomatic agents in order to circumvent the embargo imposed by the London Committee of Non Intervention. This path-breaking account reveals the operations in Spain of Mexican workers, soldiers, artists and intellectuals--such as later Nobel Laureate Octavio Paz and the Muralist David Alfaro Siqueiros--as volunteers and propagandists for the Republican cause. Engagement with the Spanish Civil War also had a profound impact upon Mexico's domestic politics as support for the Republic was equated by Cárdenas with his own revolutionary project"--Provided by publisher.